KAJIAN PERTUMBUHAN IKAN BERONANG TULIS (Siganus javus) MENGGUNAKAN PENDEKATAN VON BERTALANFFY - Salim, Gazali (Jurnal Harpodon Borneo, 2010)
Fish Siganus (Siganus Sp) is one type of fish that have high economic value, especially rabbitfishes write (Siganus javus) because these fish have a tasty meat flavor and delicious and nutritious because they contain high protein which is around 35% - 46%. By looking at the potential importance of fish Siganus javus so it will need an appropriate management through research on fish Siganus javus order to remain sustainable existence. Research on rabbitfishes has actually done that is about how to feed and cultivation of Siganus javus and Siganus Canaliculatus, but research on aspects of reproductive and morphometric rabbitfishes write (Siganus javus) is rarely done. Fish sampling was conducted from January 2004 until December 2004 by using samples taken from catches of fishermen in the waters around Jepara. This research use descriptive research design. Data collected by sampling. Data obtained from the sampling results is an estimated data (estimate value). Sampling was conducted using a purposive sampling. Based on the analysis of male fish from Demaan village, Jepara, where fish can reach a maximum length (L ∞) equal to 30.409 cm, while for female fish can reach a maximum length (L ∞) equal to 30.054 cm. Achieved by growth in rabbitfishes both male and female writing related to the availability of food in the surrounding waters in Jepara as a feeding ground or select one of the area as a place to seek food from rabbitfishes write (Siganus javus). The availability of adequate food, will make rabbitfishes writing can be grown. For the male fish will run faster growth from the age of 0-150 days, then will run very fast at the age of 150 days to 250 days age. After the age of more than 250 days, the growth in length remained relatively constant or slow down again until it reaches zero at this very old fish. Key words : Ikan Beronang Tulis (Siganus javus), Growth, Von Bertalanffy